Synthesis and Characterization of a New Cyclophosphazene and Its Ruthenium Complex Derived from 1,10-Phenanthroline-5,6-diol - Keser Karaoglan, Gulnur; Erden, Ibrahim; Demirhan, Nebahat (Asian Journal of Chemistry, 2013)
A new spirocyclic phosphazene derivative has been synthesized from the reaction of 1,10-phenanthroline-5,6-diol with hexachlorocyclotriphosphazatriene in suitable conditions and the Ru(II) complex of the ligand was prepared and characterized. Synthesized compounds have been investigated with the methods of FTIR, 1H NMR, 31P NMR, UV-VIS, MS, fluorescence and elemental analysis.